Local content requirements in WTO Law: between free trade and the right to development - Figueiredo, Natália de Lima (2022)
In the international trade arena, there has been a strong rhetoric against local content requirements (LCRs), characterising them as trade-distortive and protectionist measures that produce only inefficiencies. However, under certain circumstances, LCRs can have a central role in a countrys development process to the extent that they can potentially strengthen the domestic industrial base; create backward linkages; increase domestic value-addition in certain industries; and encourage the dissemination of knowledge and technology to the local economy. Despite this development dimension of LCRs, WTO Members policy space to implement them is reduced and the defences available under WTO law are extremely limited. Considering their potentially beneficial effects on countries development processes, WTO rules should not raise undue obstacles to the use of LCRs when they are genuinely associated with development goals and related societal concerns. Ultimately, it is widely accepted that trade is not an end in itself, but an instrument for development. In this scenario, the thesis investigates how WTO rules affecting LCRs could be interpreted to further the development objective and to what extent interpretation could mitigate the rigidness of rules that (i) were crafted in a time where mainstream economics regarded industrial policies - LCRs included - as highly inefficient and market distortive and therefore (ii) were idealised to restrict them. It concludes that panels and the Appellate Body have made use of interpretative tools that contribute to advancing the development dimension of WTO law. However, not necessarily the adjudicating bodies seize all the opportunities to further a development-oriented approach. Additionally, the thesis highlights the fact that interpretation of WTO agreements cannot be dissociated from institutional and political factors. The current institutional and political challenges of the WTO dispute settlement system and, more broadly, the multilateral system cast doubts on the feasibility of furthering a development-oriented approach to WTO rules applicable to LCRs. In particular, the current crisis of the Appellate Body caused by the political interference of the US and its strong criticism of alleged judicial activism on the part of this organ is a strong indicative that the current times are not conducive to further development in the interpretation of WTO law. In view of WTO rules prohibiting or restricting LCRs and also those institutional and political challenges, the thesis argues that there is limited space to further a development-oriented approach of WTO rules affecting LCRs without adding to or diminishing the rights and obligations of Members, contrary to the prohibition in Articles 3.2 and 9.2 of the DSU. A few opportunities, however, can still be seized by the WTO adjudicatory bodies Considering the limited scope for furthering a development-oriented interpretation, the thesis also suggests that it is necessary to review WTO rules affecting LCRs to reflect a new compromise among WTO Members on the issue. Given current political and economic scenarios, there may be some room to rediscuss LCRs in WTO law, especially because in a context of crisis, deepened by the coronavirus pandemic, WTO Members may be more willing than ever to make use of local content policies to protect their domestic economy and local jobs. Negotiations on new rules on LCRs would prevent that WTO adjudicating bodies have to deal with such sensitive issue without clearer parameters in WTO agreements, being accused of being judicially activist.